If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 47 + -6n = 11(n + 12) Reorder the terms: 47 + -6n = 11(12 + n) 47 + -6n = (12 * 11 + n * 11) 47 + -6n = (132 + 11n) Solving 47 + -6n = 132 + 11n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-11n' to each side of the equation. 47 + -6n + -11n = 132 + 11n + -11n Combine like terms: -6n + -11n = -17n 47 + -17n = 132 + 11n + -11n Combine like terms: 11n + -11n = 0 47 + -17n = 132 + 0 47 + -17n = 132 Add '-47' to each side of the equation. 47 + -47 + -17n = 132 + -47 Combine like terms: 47 + -47 = 0 0 + -17n = 132 + -47 -17n = 132 + -47 Combine like terms: 132 + -47 = 85 -17n = 85 Divide each side by '-17'. n = -5 Simplifying n = -5
| -11m-63=-11-4(8m-8) | | x+4/2=x-5/5 | | -9(1-4v)=25+2v | | -2.9=-1.2-5.2x-3.3x | | 5-8n=-8n+2 | | -2+5a+8=6+5a | | p-8=7+6p-8p | | 0=16t^2+48t+10 | | 25x-10y=-30 | | 3d^2+8d-3=0 | | -2x-6x-108=44 | | 8m^2-26m+6=0 | | 8x-16-6x=18 | | -64-11x+3x=96 | | -8x+x-70=35 | | -7-8(-3)-15+(-11)= | | x-68-7x=88 | | 7x-5x-16=24 | | -8x-31+6x=19 | | 11x+3x-109=143 | | .9x=12 | | 16x+3/2+1=0 | | 4x-x-28=53 | | -x-6x-44=82 | | 6x+9-8(x+1)=5x+6 | | 2(1+108x)=5 | | 6t^2+7t+5=0 | | y=-4x^2+14 | | 2w+2l=90 | | 4x+2=(5x+10) | | 32-9y=5y | | 2x^2+2x=20 |